2023
DOI: 10.1177/15330338221134833
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus segmentation and classification using residual SE-UNet and feature concatenation approach incervical cytopathology cell images

Abstract: Introduction: Pap smear is considered to be the primary examination for the diagnosis of cervical cancer. But the analysis of pap smear slides is a time-consuming task and tedious as it requires manual intervention. The diagnostic efficiency depends on the medical expertise of the pathologist, and human error often hinders the diagnosis. Automated segmentation and classification of cervical nuclei will help diagnose cervical cancer in earlier stages. Materials and Methods: The proposed methodology includes thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Papanicolaou's smear test is used to diagnose uterine and cervical cancer by detecting nuclear chromatin staining, size, and shape changes. 38 Whitney et al. 39 found that nuclear shape, texture and structure could independently predict the risk of recurrence in ER+ breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Papanicolaou's smear test is used to diagnose uterine and cervical cancer by detecting nuclear chromatin staining, size, and shape changes. 38 Whitney et al. 39 found that nuclear shape, texture and structure could independently predict the risk of recurrence in ER+ breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Papanicolaou's smear test is used to diagnose uterine and cervical cancer by detecting nuclear chromatin staining, size, and shape changes. 38 Whitney et al 39 found that nuclear shape, texture and structure could independently predict the risk of recurrence in ER+ breast cancer patients. This study showed that TCs nuclei circularity variance, which mainly evaluated the uniformity of nuclear roundness, was an independent prognosticator, and the greater the difference in nuclear roundness, the better the prognosis of PMP patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CNN proved its capacity to create an internal representation of the two-dimensional images, which enabled the model to represent specific locations and scales of various image features, using different elements of AI, including deep-fake [49], medicine [36,50], agriculture [51] etc.…”
Section: Cnn Modelmentioning
confidence: 99%
“…Semantic segmentation is used to classify all pixel points in an image and assign category labels. Currently, UNET [15] and its modifications [16][17][18] are extensively utilized in semantic segmentation of microscopic medical cell images. However, a significant drawback of semantic segmentation is its inability to discern between different instances of the same category.…”
Section: Introductionmentioning
confidence: 99%